Isolation and identification of halotolerant bacteria from patenga area, beach soil and land soil - Tabassum, Nafisa (BRAC University, 2017)
This Thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2016.